Pengaturan Asas Praduga Tak Bersalah (Presumption of Innocent) Pelaku Tindak Pidana Kesusilaan dalam Pemberitaan Media Massa - Putu Nia Rusmiari Dewi; I Made Wirya Darma (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This study aims to find out and analyze the regulation of the presumption of innocence contained in Article 5 Paragraph (1) of the Press Law in the mass media reporting on suspected criminal acts and to find out the legal consequences of applying the principle of presumption of innocence in media reporting on suspects of criminal acts of decency. The research method in this paper is normative which focuses on comparative law. The results of the research obtained are that the regulation of the presumption of innocence is the realization of the protection of human rights in the 1945 Constitution which is then stated in Article 8 of the Law on Judicial Power which is then used as a guarantee of justice for the protection of the rights of suspects during the criminal justice process. The legal consequence of the application of the principle of presumption of innocence is to limit the movement of the Indonesian press in reporting, especially cases that have not been decided legally by law, this right is carried out to protect the rights of suspects if later found not guilty by the court.